Steady-shear response of magnetorheological fluid containing coral-shaped yttrium-iron-garnet particles. (May 2019) - Anupama, A.V.; Choudhary, Harish K.; Kumar, Rajeev; Kumaran, V.; Sahoo, B.
Graphical abstract: Highlights: Flow behavior of YIG-based magnetorheological fluids (MRF) depends on applied magnetic field (B). The yield strength (τY ) of the MRF increases with increase in strength of B. The off-state viscosity of the MRF is high due to porous network structure of YIG-particles. The low density coral-shaped YIG particles have excellent dispersion stability in fluid. At higher B values, τY of the MRF is much higher due to particle-interlocking effects. Abstract: The steady-state magneto-mechanical response of a magnetorheological fluid (MRF), prepared by dispersing 40 wt % of magnetically soft, light-weight coral-network-shaped yttrium iron garnet (YIG; Y3 Fe5 O12 ) powder in silicone oil (140 cSt) is studied as a function of shear rate, under different applied magnetic fields (B). The results show that the yield strength (τY ) and viscosity (η) of the MRF increase with B, and are strongly influenced by the physical parameters of the particles such as morphology and saturation magnetization. The low density of the YIG-particles, leading to higher volume fraction for equal mass loading, results in a higher viscosity in the absence of a magnetic field, in comparison to that of conventional metallic Fe-particle-based MRFs. Due to this, there is a relatively smaller increase in τY and η when the magnetic field is switched on. The YIG-particles-based MRF has the advantages of high chemical stability, thermo-oxidative resistance and low-cost.